Targeting and anchoring the mechanosensitive ion channel Piezo to facilitate its inhibition of axon regeneration. - Wang, Q.; Miles, L.; Wang, S.; Ryll, L.M.; Noristani, H.N.; Schauer, E.; Monahan Vargas, E.J.; Powell, J.; O'Rourke-Ibach, S.J.; Akizu, N.; Wildonger, J.; Li, S.; et al. (PLoS Genetics, 2025)
Mechanical force orchestrates a myriad of cellular events including inhibition of axon regeneration, by locally activating the mechanosensitive ion channel Piezo enriched at the injured axon tip. However, the cellular mechanics underlying Piezo localization and function remains poorly characterized. We show that the RNA repair/splicing enzyme Rtca acts upstream of Piezo to modulate its expression and transport/targeting to the periphery of the soma via the Rab10 GTPase, whose expression also relies on Rtca. Loss or gain of function of Rab10 promotes or impedes Drosophila sensory neuron axon regeneration, respectively. Rab10 mediates the cell surface expression of integrin ?1 (Itgb1)/mys, which colocalizes and genetically interacts with Piezo, facilitating its anchorage and engagement with the microenvironment, and subsequent activation of mechanotransduction to inhibit regeneration. Importantly, loss of Rtca, Piezo1, Rab10 or Itgb1 promotes CNS axon regeneration after spinal cord injury or optic nerve crush in adult mice, indicating the evolutionary conservation of the machinery.